Advancing halal agri-food sector: Using technology and innovation for sustainable growth and new opportunities - Femdika, Donci Valentitah; Julita, Mardiana; Amara, Satya; Maisarah, Nur Ilya; Sembiring, Indra Refipal (Halal Studies and Society, 2025)
Halal agri food sector is influenced by rapid transformation driven by growing global demand, increased consumer awareness of health and ethical considerations, as well as advances in technology. Therefore, this research aimed to discuss the importance of maintaining halal integrity in food production, processing, and distribution, particularly in the era of Industry 4.0. Key drivers of innovation were explored, including the expanding Muslim population, evolving consumer preferences, and increasing sustainability concerns. The impact of technology such as blockchain, Internet of Things (IoT), and Artificial Intelligence (AI) on enhancing traceability and transparency in halal supply chain was reported. Strategies for future development comprised raising public awareness, integrating halal assurance systems with advanced technology, and strengthening collaboration among governments, industry stakeholders, and certification bodies. Significant challenges were also addressed, including fragmented global halal standards, complex certification processes, and high implementation costs. Halal agri-food sector can achieve sustainable growth and remain competitive in the global market by accepting technological innovation and enhancing cooperation among stakeholders.